Vehicles of Transportation Internal Combustion Engine Press the Details of the Institution Inspection - Dustmurodovna, Khujayarova Mokhigul (Journal of Mechanical Engineering, 2024)
In this article, the engine in the operation of vehicles details, including cylinder-piston group details, and changes in engine performance, piston rod and cylinders in the details of the cylinder when the body presses the flame-touch surface of the cylinder head redistribution of heat flow occurs, their temperature and the change of grooves in the piston-sleeve connection was analyzed. The study aims to improve the reliable performance of internal combustion engine vehicles by focusing on the maintenance and condition of the cylinder-piston group. The research includes a literature review and experimental analysis of the effects of dust and contaminants on the engine's internal components. Comparative tests were conducted on engines before and after cleaning the cylinder-piston group. Findings show that dust particles significantly impact engine performance, causing a 4-6% reduction in power and a 3-4% increase in fuel consumption. Cleaning the cylinder-piston group resulted in a 5.2% increase in engine power and a 4.0% decrease in fuel consumption. The progressive accumulation of soot was found to degrade engine efficiency and cause knocking. Regular maintenance and cleaning of the cylinder-piston group are essential to enhance engine efficiency and longevity. Implementing these practices in vehicle maintenance systems can significantly improve engine performance and reliability.